Implementation of the Learning Concept of Pancasila and Rahmatan Lil Alamin in Forming Ten Characteristics of Learners - Satriadi, Inong; Pebrina, Rizki; Syarosy, Asa; Satrial, Ardi; Waeno, Muhammadaree (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Learning Pancasila and Rahmatan Lil Alamin is character education in the independent curriculum in madrasah. The implementation of Pancasila and Rahmatan Lil Alamin in learning encourages students to explore entrepreneurial skills and creativity through approaches that are relevant to the local context. The purpose of this study is to analyze student collaboration in the implementation of Pancasila and Rahmatan Lil Alamin projects in Islamic school. The research method used is qualitative research, with multiple case designs. The informants of this research are the coordinator teacher and facilitator of the Pancasila and Rahmatan Lil Alamin project in four Islamic school in West Sumatra. Data collection used interview guidelines, observation, and documentation. The collected data were analyzed qualitatively by reducing the data according to the research objectives and presented in the form of narratives, tables, and pictures. Then to get research findings, the data were analyzed by open coding, axial coding, and selective coding. This study found that Pancasila and Rahmatan Lil Alamin activities develop the habit of collaboration between students through the theme of entrepreneurship and local wisdom. Students work in teams with various tasks and responsibilities to produce products that have creative and economic value. In addition, the acculturation of collaboration in Pancasila and Rahmatan Lil Alamin learning fosters the character of faith, devotion to God Almighty, noble character (taabud), cooperation (qudwah), independence, and creativity (tathawwur wa ibtikar), and global diversity (muwathanah and tasamuh). Thus, PRA learning can be a forum for developing the habit of working in teams and developing the creativity and potential of students who are useful for personal and community life.